2012
DOI: 10.1007/s12010-012-9878-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SPORL and Dilute Acid Pretreatment on Substrate Morphology, Cell Physical and Chemical Wall Structures, and Subsequent Enzymatic Hydrolysis of Lodgepole Pine

Abstract: The effects of pretreatment by dilute acid and sulfite pretreatment to overcome recalcitrance of lignocellulose (SPORL) on substrate morphology, cell wall physical and chemical structures, along with the subsequent enzymatic hydrolysis of lodgepole pine substrate were investigated. FE-SEM and TEM images of substrate structural morphological changes showed that SPORL pretreatment resulted in fiber separation, where SPORL high pH (4.2) pretreatment exhibited better fiber separation than SPORL low pH (1.9) pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The cell walls of woody plants often exhibit higher recalcitrance to these pretreatment processes than graminaceous plants due to higher lignin contents and denser vascular structures [ 11 ]. Acid sulfite pulping [ 12 14 ], alkaline pulping [ 15 ], organosolv pulping [ 16 ], dilute sulfuric acid pretreatment [ 17 ], liquid hot water pretreatment [ 18 , 19 ], and steam pretreatment [ 20 ] have all been successfully employed as pretreatments for woody biomass, although these processes typically require higher chemical loadings, higher temperatures, and/or longer treatment times to achieve comparable hydrolysis yields to those from grasses. Chemical pulping technologies may require substantially less severe reaction conditions when adapted as pretreatments because high levels of delignification are not required [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cell walls of woody plants often exhibit higher recalcitrance to these pretreatment processes than graminaceous plants due to higher lignin contents and denser vascular structures [ 11 ]. Acid sulfite pulping [ 12 14 ], alkaline pulping [ 15 ], organosolv pulping [ 16 ], dilute sulfuric acid pretreatment [ 17 ], liquid hot water pretreatment [ 18 , 19 ], and steam pretreatment [ 20 ] have all been successfully employed as pretreatments for woody biomass, although these processes typically require higher chemical loadings, higher temperatures, and/or longer treatment times to achieve comparable hydrolysis yields to those from grasses. Chemical pulping technologies may require substantially less severe reaction conditions when adapted as pretreatments because high levels of delignification are not required [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported 39-68% glucose conversions despite low lignin removals (5.4-6.5%) that were attributed to simultaneous depolymerization and polymerization of lignin components when reacting with sulfuric acid. Besides, as proposed by Li et al [59], it may be possible that sulfonated carbon catalysts may have disrupted the structure of lignin by the formation of hydrophobic and hydrophilic groups and may have subsequently enhanced the adsorptive interaction between cellulose and the enzyme. Therefore, from our results, it appears that sulfonic solid-impregnated carbon behaved somewhat similar to dilute acid for the pretreatment of switchgrass.…”
Section: Effect Of Sulfonic Solid Acid Pretreatment On Delignificationmentioning
confidence: 97%
“…First, it was determined that lignin removed from biomass can be used as a combustible in power generation for ethanol production facilities [43][44][45][46]. Second, not all lignin removal results in combustible lignin; in some cases, select extraction methods will modify lignin into valuable lignin byproducts, which may serve as salable co-products to reduce or offset production costs [43,45,47].…”
Section: Natural Lignin (Protolignin)mentioning
confidence: 99%